Romantic nationhood: A critique of nationalistic sentiment in the Indonesian film 5cm (2012). Issue 145 (2nd September 2021) - Kristianto, Bayu
ABSTRACT: Directed by Rizal Mantovani, the film 5cm (2012) tells the story of a group of five young Jakartans united by friendship. To test the strength of their friendship, one group member, Genta, suggests that they refrain from seeing each other for three months. At the end of this no-contact period, they climb Mount Semeru, the highest mountain in Java, and prove again the resilience of their comradeship. It is a motivational film targeted at young nature lovers which reminds the Indonesian youth of the need to love their country and its beautiful landscape. Drawing on each member's testimony of love and devotion to the Indonesian nation-state after witnessing first-hand the breathtaking wonder of Mount Semeru, I argue that the film demonstrates the subsuming of the natural environment under the power of the state, using Yi-Fu Tuan's conception of romantic geography. This analysis demonstrates how portraying nationalism romantically advocates a superficial allegiance to the nation-state and negates the sovereignty of the land.